A contribuição do processamento técnico biblioteconômico para a acessibilidade informacional - Fernandes, Joana D'Arc Páscoa Bezerra (2018)
This paper discusses the contribution of library‟s technical process for information accessibility; it conceptualizes the related terms and presents some new concepts regarding requirements for information accessibility. This work involves a deep bibliographic research in order to investigate the defined theory, for the technical work according to the Library Science that occurs in Libraries. The main purpose of the bibliographic research is to reveal what considerations in the theory may increase the quality of information accessibility. It involves the principal classification systems and the principal metadata patterns used in the subject. In addition we conducted an exploratory research as a study case. It was necessary in order to contrast the theory and the real practice in Libraries and we used a structured interview and direct observation as data gathering. The research occurred between March to May 2017. The results were grouped according to theoretical analysis, study case finds, and combined results from both.